Sequence variability in the mitochondrial 12S rRNA and tRNAVal genes of Ixodes scapularis (Acari: Ixodidae) individuals shown previously to be genetically invariant. Issue 3 (June 2015) - Krakowetz, Chantel N.; Sproat, Allison; Lindsay, L. Robbin; Chilton, Neil B.
Abstract: The DNA sequences of the mitochondrial (mt) 12S rRNA and tRNA Val genes were characterized for 82 blacklegged ticks ( Ixodes scapularis ) that were genetically identical for Domains IV and V of the mt 16S rRNA gene. Thirty-one haplotypes, differed in sequence by 1–9 bp, were detected among the 82 ticks. Most nucleotide alterations in DNA sequence did not affect the stability of the secondary structures of the RNAs. The magnitude of the DNA sequence variation in the mt 12S rRNA and tRNA Val genes among blacklegged ticks suggests that this region of the mitochondrial genome has potential as a genetic marker for examining the population genetics and phylogeography of I. scapularis .